Clinical anatomy of the neck - Tuyg‘unbekov Kamoliddin, Gadayev Asliddin (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
The clinical anatomy of the neck is a complex area of study that is essential for understanding the structures and functions of the neck region. The neck is a vital part of the human body, containing a multitude of important anatomical structures that have a significant impact on overall health and well-being. A comprehensive understanding of the clinical anatomy of the neck is crucial for healthcare professionals, including physicians, surgeons, and medical students, as it forms the basis for assessing and diagnosing a wide range of medical conditions and performing surgical interventions in the neck region.